1990
DOI: 10.1159/000235177
|View full text |Cite
|
Sign up to set email alerts
|

Drugs as Allergens: An Immunoassay for Detecting IgE Antibodies to Cephalosporins

Abstract: A radioimmunoassay employing cephalothin linked to a solid phase has been developed for the detection of cephalosporin-reactive IgE antibodies. Direct binding and inhibition studies demonstrated allergenic cross-reactivity between cephalosporins and penicillins, and quantitative hapten inhibition experiments identified the 2-thiophene group, and particularly the attached methylene group, of cephalothin as an allergenic determinant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 8 publications
3
43
0
Order By: Relevance
“…Employment of benzylpenicilloyl (BPO)-and the so-called cephalosporoyl (CephO)-solid phases in hapten inhibition tests with the two parent drugs, together with molecules representing their side chains viz., phenylacetic acid, benzylamine and 2-thiophene acetic acid; the β-lactam structure without side chain (6-aminopenicillanic acid); and the β-lactam ring structure (azetidinone) indicated that the methylene group in the side chains of each of the two drugs is a dominant feature of the cross-reactive IgE-binding determinant (Figure 5a,b) [19]. The results were similar to earlier quantitative inhibition findings employing an immunoassay for cephalosporin-reactive IgE in the sera of patients allergic to cephalothin [20] and further suggested that as well as the methylene structure, the thiophene ring acts as a bioisostere of the benzene ring in the side chain of benzylpenicillin [19]. Another good example of the preferential recognition of the penicillin R side chain was provided by the demonstration of IgE antibodies complementary to phenylisoxazolyl R substituents in the sera of patients who experienced anaphylaxis following the administration of flucloxacillin [17].…”
Section: Reaction Of Penicillins With Ige Antibodies and Identificatisupporting
confidence: 88%
See 1 more Smart Citation
“…Employment of benzylpenicilloyl (BPO)-and the so-called cephalosporoyl (CephO)-solid phases in hapten inhibition tests with the two parent drugs, together with molecules representing their side chains viz., phenylacetic acid, benzylamine and 2-thiophene acetic acid; the β-lactam structure without side chain (6-aminopenicillanic acid); and the β-lactam ring structure (azetidinone) indicated that the methylene group in the side chains of each of the two drugs is a dominant feature of the cross-reactive IgE-binding determinant (Figure 5a,b) [19]. The results were similar to earlier quantitative inhibition findings employing an immunoassay for cephalosporin-reactive IgE in the sera of patients allergic to cephalothin [20] and further suggested that as well as the methylene structure, the thiophene ring acts as a bioisostere of the benzene ring in the side chain of benzylpenicillin [19]. Another good example of the preferential recognition of the penicillin R side chain was provided by the demonstration of IgE antibodies complementary to phenylisoxazolyl R substituents in the sera of patients who experienced anaphylaxis following the administration of flucloxacillin [17].…”
Section: Reaction Of Penicillins With Ige Antibodies and Identificatisupporting
confidence: 88%
“…Examination of the specificities of penicillin-reactive IgE antibodies in the serum from a number of allergic patients revealed a heterogeneous group of allergenic determinants consisting exclusively, or in part, of the side chain groups of penicillins, the β-lactam ring and the thiazoline ring [16][17][18][19][20]. In some patients the entire penicillin molecule comprises the IgE-binding determinant structure.…”
Section: Reaction Of Penicillins With Ige Antibodies and Identificatimentioning
confidence: 99%
“…Despite the lack of certainty about the chemical structure of the antigenic determinant responsible for allergic reactions to cephalosporins, several studies (Pham and Baldo, 1996;Baldo, 1999;Harle and Baldo, 1990) have reported immunological results, although the conclusions have to be taken with a certain degree of speculation. Because the haptenic determinant of cephalosporins produced by their degradation is largely unknown, more definite studies require each free drug to be used as the skin test agent to detect antibodies reactive to these antibiotics (Baldo, 1999;Weiss and Adkinson, 1988).…”
Section: Immunochemical Studiesmentioning
confidence: 99%
“…Cross-reaction between penicillins and cephalosporins generally involve first and second-generation cephalosporins (9). The possibility of development of cross-reaction against penicillins in patients with advers reactions solely against thirdgeneration cephalosporins is lower compared to first-generation cephalosporins, since first-generation cephalosporins are structurally more similar to penicillins (10). The risk of allergic reactions related to ceftriaxone because of cross-reaction is expected to be higher in patients known to have a previous history of allergy against beta-lactam group of antibiotics.…”
Section: Discussionmentioning
confidence: 99%